Fluid identities : contextualising genital reconstructive surgery after female circumcision in Burkina Faso : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Social Anthropology at Massey University, Auckland, New Zealand. - Nyarango, Margaret (Massey University, 2016)
Female circumcision procedures were traditionally performed on many girls and women in Burkina Faso. These practices were outlawed in 1996, and are now termed ‘female genital mutilation’ by the government and activists trying to stop them. About thirtyfive years ago, Pierre Foldès, a French urologist who was on a humanitarian mission to West Africa, developed a surgical procedure to alleviate health problems associated with these practices. He later refined his procedure and started using it to also restore clitoral anatomy and function. This surgery, which is presented as two distinct procedures in Burkina Faso, is now performed by some indigenous doctors in Ouagadougou and Bobo-Dioulasso. In this ethnographic study, I explore the reasons motivating some Burkinabe women to seek genital reconstructive surgery, the impact this surgery has on them and societal attitudes towards this surgery and these women. I discuss concepts of gender and embodiment in relation to Burkinabe girls’ and women’s health and sexuality by considering their understanding of what is normal, healthy, natural, complete, sexually attractive and feminine. I also consider the manner in which the meanings of these notions are changing depending on the prevailing discourse. I argue that the salience of the discourse promoted by the Burkinabe government and activists working to end female circumcision in the urban areas of Burkina Faso is compounding the harm associated with this practice. It has led some circumcised women to view themselves, and to be viewed by others, as unhealthy and sexually defective, and to believe that they need genital reconstructive surgery. Yet, limited information about this surgery, its cost and taboos associated with sex and sexuality limit women’s access to the surgery. I further argue that that some Burkinabe women in the Raëlian Movement are co-opting the discourse that paints circumcised women as victims to create spaces where they can remodel typical Burkinabe values, but also exercise those which are particular to their religion. They have thus embraced genital reconstructive surgery to reconstruct not just their bodies, but also their identity as healthy and sensual women.
Keywords: Surgery, Plastic; Female circumcision; Social aspects; Social conditions; Burkina Faso